2020
DOI: 10.1016/s2213-8587(20)30336-3
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the COVID-19 pandemic in paradise: the Mauritian experience

Abstract: al. Urine steroid metabolomics for the differential diagnosis of adrenal incidentalomas in the EURINE-ACT study: a prospective test validation study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Over the next few days, the Chinese Centre for Disease Control and Prevention (CDC) started to investigate the possible causes of these new and strange presentations. A new virus was finally identified and found to belong to the family of coronavirus (CoV) which also included severe acute respiratory syndrome coronavirus (SARS-CoV), discovered in 2002, and the Middle East respiratory syndrome coronavirus (MERS-CoV) which appeared in 2012 [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the next few days, the Chinese Centre for Disease Control and Prevention (CDC) started to investigate the possible causes of these new and strange presentations. A new virus was finally identified and found to belong to the family of coronavirus (CoV) which also included severe acute respiratory syndrome coronavirus (SARS-CoV), discovered in 2002, and the Middle East respiratory syndrome coronavirus (MERS-CoV) which appeared in 2012 [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have also BMJ Global Health pinpointed the rapid response by the Mauritian Government, and appropriate and strong support and compliance from the public as key factors towards the control of the pandemic. 5 A retrospective study using inferential statistical methods identified a number of factors that have contributed significantly in controlling the propagation of the novel coronavirus in Mauritius; in particular, the sanitary curfew/lockdown, sanitisation and sensitisation campaigns, and safe shopping guidelines have helped to curb down, by a large extent, the number of COVID-19 cases. Hence, such preventive and proactive measures, with the main focus on sanitisation measures at grocery stores and in busy public places, should be maintained even after lifting lockdown orders.…”
Section: Resultsmentioning
confidence: 99%
“…With the escalation of cases, a curfew was imposed on 20 March, and eventually a complete lockdown was implemented on 24 March. 5 According to the national surveillance system, the outbreak quickly evolved from sporadic cases to clusters and then to local transmission and was contained on 26 April 2020, after 39 days, with no locally transmitted cases until November 2020. Then, two new community cases were reported, and since 26 November, only imported cases have been reported in the island.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 originates from the coronavirus family and is an enveloped, single-stranded RNA virus. Two other members of that family of virus include severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) [ 1 , 7 ]. SARS appeared between 2001 and 2003, causing the deaths of 774 people.…”
Section: Virology: What Is Sars-cov-2?mentioning
confidence: 99%
“…They have shut down their international borders, and all passengers are required to undergo quarantine as well as multiple tests to rule out any trace of COVID-19. They also issued strict lock-downs, and it was illegal to spread any misinformation on social media regarding the pandemic [ 7 ].…”
Section: Major Hurdles During the Year And What To Expect Nowmentioning
confidence: 99%